4ARTPRENEUR: Competences for entrepreneurship in Art and Cultural Industries - Jiménez, Esther; Urbano, Judith (TECHNO REVIEW. International Technology, Science and Society Review /Revista Internacional de Tecnología, Ciencia y Sociedad, 2022)
The Europe 2020 strategy recognizes that entrepreneurship is essential to promote job growth, given the opportunities and challenges arising from the structural changes that are taking place. The project 4ArtPreneur has joined a group of universities and institutions with the aim of developing a course on entrepreneurship at schools and faculties of cultural and creative industries (CCI). Through an innovative methodology they will learn the complexity of the art market, basic models of funding and marketing strategies of the CCI.